Challenges and Strategies of Implementing Financial Accounting Standards Recording for Muslim EMKM MSME at PT. Keloria Moringa Jaya - Isra Hayati; Syahrani Devi; Alfi Amalia; Titis Budi Prihatin (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to analyze the challenges faced by MSMEs in implementing SAK EMKM and formulate strategies to encourage compliance with these standards. This study uses a qualitative approach with data collection techniques using SAK EMKM interviews. The results of the study indicate that the main challenges in implementing SAK EMKM include: (1) low understanding and awareness of MSME actors about SAK EMKM; (2) limited human resources who have competence in accounting; (3) no separation between business and personal transactions; (4) less supportive cost-benefit perceptions; and (5) lack of socialization and mentoring. The strategies formulated include: (1) strengthening tiered education and socialization programs; (2) establishing a sustainable mentoring system; (3) developing technology-based accounting applications that comply with SAK EMKM; (4) strengthening the role of financial institutions in encouraging compliance; and (5) collaboration between academics, practitioners, regulators, MSME actors, and financial institutions.